Electromagnetic Propagation and Waveguides in Photonics and Microwave Engineering - Steglich, Patrick; Steglich, Patrick (IntechOpen, 2020)
Optical and microwave waveguides have attracted much research interest in both science and industry. The number of potential applications for their use is growing rapidly. This book examines recent advances in the broad field of waveguide technology. It covers current progress and latest breakthroughs in emergent applications in photonics and microwave engineering. The book includes ten contributions on recent developments in waveguide technologies including theory, simulation, and fabrication of novel waveguide concepts as well as reviews on recent advances.
English
Keywords: Optical physics; Electricity, electromagnetism & magnetism